INTEGRATION OF ALEF CONTENT INTO MOODLE LMS TO SUPPORT DIGITAL LEARNING AT SMP NEGERI 1 KOLAKA - Sanjani, Ade Riska; Nasrum, Akbar; Sari, Dian Ulfa (Universitas Sembilanbelas November Kolaka, 2025)
The digital transformation in education demands the development of adaptive and effective learning media. This study aims to develop digital learning media by integrating Alef Education content into the Moodle Learning Management System (LMS) platform at SMP Negeri 1 Kolaka. The research employed a Research and Development (RD) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation results from media and content experts indicate that the developed learning media is highly valid, with scores of 87.78% and 92%, respectively. Analysis of student and teacher response questionnaires shows that the media is practical, with practicality scores of 77% and 68%. The study concludes that the collaboration between Alef content and Moodle LMS positively impacts the quality of learning. Further research is recommended to develop Alef content for varying student ability levels and to explore its implementation in other schools.